Parental Expectations of Pre-school Children. An empirical study of their role and their determinants - Stamm, Margrit; Edelmann, Doris (Swiss Journal of Educational Research, 2018)
It is a frequently proven empirical fact that the behaviour of parents has considerable influence on their child development. However, only a few studies examine the role their expectations play in the area of early childhood education. This contribution presents results provided by a Swiss pilot study about the expectations parents (200 fathers and 200 mothers) report to have for their pre-school children. Results show that fathers indicate significantly higher expectations than mothers with regard to the development of the academic, motor, athletic, artistic, and musical skills of their child, but not with regard to his/her social behaviour development. The most important variable influencing parental responses is the time devoted to primary care. Parents spending more than fifteen hours per week with their child, have greater expectations regarding the skills and behaviour development of their child than parents spending less time on primary care.